Three new species and DNA sequence data of the rare South American water beetle genus Adelphydraena Perkins, 1989 (Coleoptera: Hydraenidae) - Perkins, Philip D.; Ribera, Ignacio (Zootaxa, 2020)
Three new species of the very rarely collected water beetle genus Adelphydraena Perkins, 1989 are described from Brazil, Guyana, and Suriname. Illustrations of the male genitalia of the two previously known species in the genus, A. orchymonti Perkins and A. spangleri Perkins from Venezuela, are presented for the first time. High resolution digital images of the habitus of all species are given, and geographical distributions mapped. New species described are Adelphydraena amazonica n. sp. (Brazil), A. spinosa n. sp. (Guyana), and A. surinamensis n. sp. (Suriname). Mitochondrial and nuclear DNA sequence data is given for three of the five species currently known (A. orchymonti, A. spangleri, and A. amazonica). The monophyly of the genus Adelphydraena was strongly supported, but relationships between the sequenced species remain uncertain.